Alternative perspectives of the angling community on Eurasian beaver (Castor fiber) reintroduction in the River Otter Beaver Trial. Issue 7 (7th June 2021) - Auster, Roger Edward; Barr, Stewart; Brazier, Richard
Abstract : Eurasian beaver ( Castor fiber ) reintroduction is taking place in England with potential benefits for flood alleviation and biodiversity; however there is also opposition. One area of controversy relates to fish and fishing. A previous meta-analysis of research into beaver-fish relationships found perceived benefits of beavers amongst fish and beaver "experts" included increased fish abundance and productivity, whilst perceived negatives included impeded fish passage and reduced spawning habitat availability. We further this understanding using Q-Methodology (a social science technique) to reveal three nuanced and contrasting perspectives that exist amongst the angling community in the catchment of a trial reintroduction. Due to a conflict potential between groups, we suggest management themes to help reduce this where reintroduction occurs: open, cross-sectoral dialogue about research into beaver-fish relationships and management; a management strategy which supports ecosystem benefits whilst providing a sense of empowerment for individuals to respond to negative impacts.